Accessing occupational exposure to fungi in a cork industry - Viegas, C. (2016)
In this study we aimed to access fungal exposure in workers from one cork industry through the mycological analysis of their nasal exudate and the environmental fungal contamination of their surroundings as well. Nasal mucous samples from 127 workers were taken with sterilized cotton swabs.The fungal species identified in the collected nose swabs were shown to be correlated with the results obtained in the environment. Eighty workers (63.0%) presented contamination of their nose nostril with Chrysonilia sitophila, which number of colonies was countless. Within the Aspergillus genus, the complexes Fumigati, Circumdati, Versicolores and Candidi were isolated. No azole-resistant Aspergillus isolates grew in the selective media used (screened itraconazole and voriconazole resistance).This approach allowed us to estimate the risk associated with these tasks performance. Moreover, the cork industry is related to high dust contamination and this can promote exposure to fungi since dust particles can act as carriers of fungi to the worker’s nose. Assessment by molecular tools will ensure the specific targeting of DNA from P. glabrum complex in workers nose.